2022
DOI: 10.1101/2022.12.13.520352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Translational Tissue Engineering Approach to Airway Reconstruction Leveraging Decellularized Meniscus and Cartilage Progenitor Cells

Abstract: Severe subglottic stenosis develops in over 20,000 infants per year and requires laryngotracheal reconstruction (LTR) to enlarge the airway by implanting autologous cartilage from a rib graft. However, young children often lack sufficiently sized costal cartilage resulting in increased donor site morbidity and operative time, as well as an elevated risk for airway restenosis necessitating revision surgery. To overcome these limitations, we have created a first-of-its-kind scaffold based on porcine meniscal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…There, in a LTR study of 38 rabbits, MEND expanded the airway and integrated with the adjacent cartilage, marked by an increase in glycosaminoglycans (GAGs) and neochondrification. 28 Although our previous study demonstrated the effectiveness of MEND as a graft for LTR, we are proposing to use MEND as an LTR graft in pediatric patients, and the rabbits of our previous study were adults. In fact, all animal studies published to test tissue engineered LTR grafts involved only adult animals, 29 which do not accurately recapitulate the complex growing environment of the pediatric airway or children undergoing LTR.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There, in a LTR study of 38 rabbits, MEND expanded the airway and integrated with the adjacent cartilage, marked by an increase in glycosaminoglycans (GAGs) and neochondrification. 28 Although our previous study demonstrated the effectiveness of MEND as a graft for LTR, we are proposing to use MEND as an LTR graft in pediatric patients, and the rabbits of our previous study were adults. In fact, all animal studies published to test tissue engineered LTR grafts involved only adult animals, 29 which do not accurately recapitulate the complex growing environment of the pediatric airway or children undergoing LTR.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous study successfully used MEND to engineer cartilage in vitro that mimicked the biochemical content and mechanical strength of the cricoid. There, in a LTR study of 38 rabbits, MEND expanded the airway and integrated with the adjacent cartilage, marked by an increase in glycosaminoglycans (GAGs) and neo‐chondrification 28 . Although our previous study demonstrated the effectiveness of MEND as a graft for LTR, we are proposing to use MEND as an LTR graft in pediatric patients, and the rabbits of our previous study were adults.…”
Section: Introductionmentioning
confidence: 99%